1996
DOI: 10.1111/j.1559-1816.1996.tb02729.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Attractiveness and Sexual Harassment: Does Every Picture Tell a Story or Every Story Draw a Picture?1

Abstract: The role of physical attractiveness in perceptions of sexual harassment (SH) was investigated in two studies. In the first study, 164 undergraduates were given a complainant's description of either a verbal or physical incident of SH. Photographs varying physical attractiveness of the alleged harasser and victim were provided. Results showed gender differences in perceptions of incident characteristics and an attractiveness bias for both harasser and victim. There was evidence that characteristics of the setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 5 publications
0
15
1
3
Order By: Relevance
“…Specifically, perpetrator attractiveness did not influence believability or punishment. These findings are not consistent with the conclusions of Golden et al (2001) and Popovich et al (1996), who found that physically attractive perpetrators were viewed more positively than unattractive perpetrators. However, our results do support the "what is beautiful is good" stereotype (Dion, Berscheid, & Walster, 1972;Hatfield & Sprecher, 1986), which reveals that the attractiveness effect is stronger in social domains (e.g., likeability) than in other domains (e.g., believability; Eagly et al, 1991).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Specifically, perpetrator attractiveness did not influence believability or punishment. These findings are not consistent with the conclusions of Golden et al (2001) and Popovich et al (1996), who found that physically attractive perpetrators were viewed more positively than unattractive perpetrators. However, our results do support the "what is beautiful is good" stereotype (Dion, Berscheid, & Walster, 1972;Hatfield & Sprecher, 1986), which reveals that the attractiveness effect is stronger in social domains (e.g., likeability) than in other domains (e.g., believability; Eagly et al, 1991).…”
Section: Discussioncontrasting
confidence: 79%
“…Behaviors of attractive perpetrators tend to be perceived more positively than those of unattractive perpetrators. For example, a study by Popovich et al (1996) showed that physically attractive perpetrators were viewed more positively than unattractive perpetrators in that scenarios were rated as more innocuous when perpetrators were physically attractive than when they were unattractive. Similarly, LaRocca and Kromrey (1999) examined the effects of attractiveness on the perceptions of sexual harassment under ambiguous conditions and found that the ambiguous behavior was rated as less harassing when the perpetrator was attractive.…”
Section: Physical Attractivenessmentioning
confidence: 95%
See 1 more Smart Citation
“…In simulated rape cases, researchers have found that the accused rapist of an attractive victim was more likely to be seen as guilty than was an accused rapist of an unattractive victim (Jacobson, 1981;Jacobson & Popovich, 1983). In a study that simulated a sexual harassment case in a business setting, both female and male participants, playing the role of a personnel director evaluating an allegation of sexual harassment, were more likely to believe that the incident was sexually motivated when the female victim was physically attractive than when she was not (Popovich et al, 1996). Those authors speculated that this effect may have resulted from "pre-established beliefs about SH-that a woman must be attractive to elicit the attentions of a man (even in a harassment situation)" (p. 532).…”
Section: Discussionmentioning
confidence: 93%
“…Some research in psychology indicates that the same visual images can be recognized and interpreted differently by men and women (Greene & Fraser, 2002;Katsikitis, Pilowsky, & Innes, 1997;Kirouac & Dore, 1985;Popovich et al, 1996). For example, Barrett and Barrington (2005) found that women are influenced more by a positive picture and men triggered by a negative one.…”
Section: Personal Experience and Characteristicsmentioning
confidence: 94%